Palm oil farmers’ welfare: a geographical information system approach - Suhartono, Suhartono; Rahayu, Heffi Christya; Hidayat, Hidayat; Indramawan, Dendy (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
This study analyzes the welfare paradox in Rokan Hulu Regency, where abundant natural resources coexist with low community welfare. Using the Lorenz curve and Gini index, spatial mapping was employed to create a socio-demographic map. Primary data were analyzed with the Slovin method and Gini index models. Results show high inequality, with Gini index values of 0.81 (income-based) and 0.84 (expenditure-based). To address this, the government can support oil palm farmers through policies on fertilizer subsidies, worker wage regulation, and standardized palm oil pricing, aiming to improve the economic conditions of the farming community.